Development of environmental benchmarks for the Belgian residential building stock. Issue 1 (1st September 2022) - Mouton, L; Trigaux, D; Allacker, K; Crawford, R H
Abstract: Over recent years Belgium has made meaningful effort in adopting Life Cycle Assessment (LCA) in building practice to improve building environmental performance. Today, architects can compare the environmental performance of different building designs with an online calculation tool that incorporates the national LCA method. However, they are still lacking environmental benchmarks to position themselves within current building practice. Furthermore, such benchmarks play an important role in the development of environmental targets in building regulation. In this research, benchmarks are defined for new residential buildings in Belgium. A bottom-up approach is followed consisting of a statistical analysis of reference buildings to define limit, reference and best practice values. The buildings are based on four representative typologies for Belgium, ranging from detached houses to apartments. Different variants are assessed including various energy performance levels and construction types (solid versus timber). The buildings' life cycle impacts are calculated including the embodied (material) and operational (energy) impacts. Results are reported both for an aggregated environmental single-score and for Global Warming Potential (GWP). The calculated reference values for life cycle and embodied GWP (20 and 7 kgCO2 eq/m 2 .year) are comparable to existing benchmarks in the literature. The results further highlight that building compactness provides the largest impact reduction, followed by construction type. Finally, limitations are discussed and recommendations are formulated for developing future benchmarks.